2011
DOI: 10.1088/2041-8205/742/2/l30
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Pion Emission From Accelerated Protons in the Supernova Remnant W44

Abstract: We present the AGILE gamma-ray observations in the energy range 50 MeV -10 GeV of the supernova remnant (SNR) W44, one of the most interesting systems for studying cosmic-ray production. W44 is an intermediate-age SNR (∼ 20, 000 years) and its ejecta expand in a dense medium as shown by a prominent radio shell, nearby molecular clouds, and bright [SII] emitting regions. We extend our gamma-ray analysis to energies substantially lower than previous measurements which could not conclusively establish the nature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
122
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(129 citation statements)
references
References 44 publications
7
122
0
Order By: Relevance
“…The most plausible source appears to be supernovae remnants (SNRs) and is consistent with X-and gamma-ray data for electron and hadron acceleration respectively [11][12][13]. However the Fermi bubbles could be another powerful accelerator in our galaxy.…”
Section: Introductionsupporting
confidence: 69%
“…The most plausible source appears to be supernovae remnants (SNRs) and is consistent with X-and gamma-ray data for electron and hadron acceleration respectively [11][12][13]. However the Fermi bubbles could be another powerful accelerator in our galaxy.…”
Section: Introductionsupporting
confidence: 69%
“…Modeling of the broadband spectra from such SNRs, in order to ascertain the nature of the γ -ray emission, is complicated and has led to mixed interpretations, making the evidence for ion acceleration controversial in some cases. Gamma-ray emission from some SNRs known to be interacting with molecular clouds seems to require a significant component from pion decay (e.g., Abdo et al 2009Abdo et al , 2010Castro & Slane 2010;Giuliani et al 2011;Ackermann et al 2013), with some remnants requiring nearly all of the SNR kinetic energy to be converted to relativistic electrons for IC emission to dominate the flux (Castro et al 2013;Auchettl et al 2014). For W44 and IC 443, the γ -ray spectra show clear evidence of a kinematic "pion bump," firmly establishing the presence of energetic ions in these remnants (Ackermann et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to their excellent sensitivities, Cherenkov telescopes on the ground and the Large Area Telescope (LAT) on board the Fermi satellite have detected a few tens of SNRs with good spectral measurement in the γ-ray range during the past decade (Ferrand & Safi-Harb 2012;Carrigan et al 2013;Acero et al 2016), revealing a variety of γ-ray spectra . Moreover, analyses of Fermi-LAT and AGILE observations of SNRs W44, IC443 (Tavani et al 2010;Giuliani et al 2011;Ackermann et al 2013), and W51C (Jogler & Funk 2016) have revealed tentative evidence for a low-energy spectral turnover associated with the p 0 decay process.…”
Section: Introductionmentioning
confidence: 99%